(untitled) (REMUNOM, 2023)
Abstract: The article analyzes the process of occupation and settlement of the hinterland of São Francisco north of Minas Gerais, the emergence of private power to the detriment of public power and the installation of a network of local command based on kinship. In this perspective, the networks of sociability in the hinterland are perceived through the narratives that the colonial authorities uttered about this region in the 18th century. This work is bibliographical and documental in nature, therefore, the documentation used for its development consisted of book 10 of Manuscritos do Brasil, belonging to the National Archive Torre do Tombo (ANTT) of Portugal, of the codices of the Colonial Section of the Publico Mineiro in Belo Horizonte (SC/APM), in addition to the bibliography research in theses, dissertations, books, and articles that used these documents as a means of perceiving its uniqueness in the backlands of São Francisco.